Quantifying the Impact of Tradeon Wages : The Role of Nontraded Goods - Tokarick, Stephen (IMF Working Papers; Working Paper ;, 2002)
This paper uses an applied general equilbrium model to decompose the effects of changes in trade and technology-related variables on wages of skilled and unskilled labor between 1982 and 1996 in the United States. The results indicate that trade-related variables (tariff cuts, improvement in the terms of trade, and the increase in the trade deficit) had little impact on the widening wage gap. Also, changes in total factor productivity had a small effect on relative wages. The major factor behind the rise in the skilled wage relative to the unskilled wage was differential rates of growth in skill-biased technical change across sectors. The paper also highlights the role that nontraded goods play in explaining the wage gap. Finally, the paper presents estimates of the effect of trade on wages by calculating what wage rates would be under autarky. The results show that expanding trade could actually reduce wage inequality, rather than increase it. The welfare costs to the U.S economy of moving to autarky (using 1996 as a base) are about 6 percent of GDP.